Identification of small fiber neuropathy in neuronal intranuclear inclusion disease: A clinicopathological study - Liu, Minglei; Liu, Ruoyu; Yuan, Yanpeng; Liu, Xiaojing; Li, Lanjun; Wang, Yangyang; Yuan, Jing; Zhang, Ke; Li, Shuo; Yang, Ting; Wang, Yanlin; Gao, Yuan; et al. (Alzheimer's & dementia, 2025)
INTRODUCTION Neuronal intranuclear inclusion disease (NIID) manifests as dementia combined with other neurological symptoms. However, small fiber neuropathy (SFN) and pathology remain unknown in NIID. METHODS A total of 294 subjects, including patients with NIID, Parkinson's disease, Alzheimer's disease, diabetic peripheral neuropathy, and healthy controls (HCs), were included. Clinical scales, sensory and autonomic function testing, and skin biopsy were performed. RESULTS NIID patients had more severe sensory and autonomic dysfunction than other groups. Substantial reductions in intraepidermal, sweat gland, and pilomotor nerve fiber densities were observed in NIID patients, with a non–length dependent pattern. Detailed analysis revealed marked reductions in noradrenergic, cholinergic, peptidergic, and regenerative nerve fibers. Small fiber densities showed high diagnostic accuracy in distinguishing NIID from HCs and other diseases. DISCUSSION This study is the first to reveal wide and severe loss of small fibers in NIID, suggesting the involvement of SFN in the pathogenesis of NIID. Highlights Our study is the first to identify wide and severe non–length dependent small fiber neuropathy in neuronal intranuclear inclusion disease (NIID) patients. Approximately 50% of NIID patients exhibited pure small fiber neuropathy without large fiber or mixed neuropathy. NIID patients showed a significant reduction in noradrenergic, cholinergic, peptidergic, and regenerative fiber innervation. Small fiber densities, especially intraepidermal nerve fiber density, demonstrated high diagnostic accuracy in distinguishing NIID patients from healthy controls and other disease groups. Findings suggest that small fiber neuropathy may play a role in the pathogenesis of NIID.